2015
DOI: 10.1002/mgg3.126
|View full text |Cite
|
Sign up to set email alerts
|

Improved inherited peripheral neuropathy genetic diagnosis by whole‐exome sequencing

Abstract: Inherited peripheral neuropathies (IPNs) are a group of related diseases primarily affecting the peripheral motor and sensory neurons. They include the hereditary sensory neuropathies (HSN), hereditary motor neuropathies (HMN), and Charcot-Marie-Tooth disease (CMT). Using whole-exome sequencing (WES) to achieve a genetic diagnosis is particularly suited to IPNs, where over 80 genes are involved with weak genotype–phenotype correlations beyond the most common genes. We performed WES for 110 index patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
3
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 57 publications
4
55
3
12
Order By: Relevance
“…Inversely, the p.Arg409Trp mutation was reported to result a less severe phenotype than that of a patient with two mutations (p.Ser382Arg and p.Asp383Tyr) representing the most severe phenotype of the CHN [12]. EGR2 mutations may cause a variety of peripheral neuropathies [4]. Our case supports the hypothesis that EGR2 p.Arg359Trp results in early onset BSA phenotype with severe and rapid evolution.…”
supporting
confidence: 79%
“…Inversely, the p.Arg409Trp mutation was reported to result a less severe phenotype than that of a patient with two mutations (p.Ser382Arg and p.Asp383Tyr) representing the most severe phenotype of the CHN [12]. EGR2 mutations may cause a variety of peripheral neuropathies [4]. Our case supports the hypothesis that EGR2 p.Arg359Trp results in early onset BSA phenotype with severe and rapid evolution.…”
supporting
confidence: 79%
“…The observed lack of BICD2 mutations in HSMN patients is in line with the results of a recent study describing whole exome sequencing for 110 index patients with HMSN. Two novel heterozygous missense mutations, p.(Ala360Val) and p.(Val665Leu), were discovered, each in a single patient, but bioinformatics tools suggested that they may constitute rare variants rather than disease‐causing mutations . Overall, the interpretation of missense mutations still poses considerable challenges for genetic researchers and diagnostic specialists, and it has been estimated that even a considerable number of variants classified as disease‐causing in common databases may instead be rare variants …”
Section: Discussionmentioning
confidence: 99%
“…Further, because hereditary motor and sensory neuropathy (HMSN) may also show overlapping symptoms with SMALED, we investigated the presence of BICD2 mutations in a cohort of HMSN patients. To date, in one study performing whole exome sequencing in patients with HMSN, 2 previously unreported missense variants were described in the BICD2 gene, but bioinformatics analyses suggested these were most likely nonpathogenic variants …”
mentioning
confidence: 99%
“…As an example, a variant in the Senataxin gene ( SETX ) reported as a putative mutation was finally confirmed as a non-pathogenic rare polymorphism [30]. Also, the implication of the gene in the pathology should be recognized, i.e.…”
Section: Outcomes Of Mps For Nmd In a Diagnosis Settingmentioning
confidence: 99%